lncRNA-LET Regulates Glycolysis and Glutamine Decomposition of Esophageal Squamous Cell Carcinoma Through miR-93-5p/miR-106b-5p/SOCS4 - Su, Xincheng; Xue, Cong; Xie, Chengke; Si, Xianzhe; Xu, Jie; Huang, Wenbo; Huang, Zhijun; Lin, Jianqing; Chen, Zhiyao (Frontiers in Oncology, 2022)
Background: Dysregulated non-coding RNAs exhibit critical functions in various cancers. Our previous study had also shown that the lncRNA-LET is closely related to the esophageal squamous cell carcinoma (ESCC). Nonetheless, the levels and functions of lncRNA-LET within ESCC remain to be elucidated. Methods: Initially, the aberrant low lncRNA-LET levels within ESCC tissues are validated via qRT-PCR observations. Moreover, we determine how lncRNA-LET upregulation affects cell proliferation in vitro. In addition, a serry of assays determining the mechanistic views related to the metabolism are conducted. Further, the effects of lncRNA-LET in affecting tumor growth are investigated in vivo in a mouse model. The interactions between lncRNA-LET and its networks are predicted and further determined by RNA immunoprecipitation (RIP)-assisted qRT-PCR and luciferase reporter assays. Results: lncRNA-LET down-regulation correlates to the poor prognosis of ESCC patients. The cell viability could be inhibited due to up-regulated expression of lncRNA-LET. In vivo tumor inhibition efficacy assays showed that an increase of lncRNA-LET presented excellent inhibitory effects on cancer proliferation, reflected by tumor weight and volume in mice.Mechanistic views regarding the effects of mir-106b-5p or mir-9-5p, SOCS4 on ESCC are related to the feedback of lncRNA-LET. Conclusion: Collectively, this study suggested that lncRNA-LET mir-9-5p or mir-106b-5p-SOCS4 axis may contribute to treating ESCC.